Old Sarum
This particular Iron Age fortress remained as a settlement until recent times. The Normans built a motte and a cathedral on the site, which was replaced in 1228 by the Cathedral at Salisbury, and, although by the 19th century there were no longer any dwellings, a member of Parliament has regularly returned. The structure consists of concentric earthwork banks, as at Cley Hill and at other Iron Age sites.